ANALISIS KEPEMIMPINAN DAN IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DI SDN 16 LIANGENG - Suci Ramadani; Suardi (STKIP Subang, 2026)
This study aims to analyze the principal’s leadership practices in the implementation of School-Based Management (SBM) at SDN 16 Liangeng, identify the challenges and opportunities of its implementation, and formulate strategies to strengthen a collaborative and participatory culture in improving the quality of primary education. A qualitative approach was employed through interviews, observations, document analysis, and focus group discussions involving the principal, teachers, school committee members, students, and Master’s students in Primary Education as field observers. The findings indicate that the principal has demonstrated transformational leadership practices through openness to ideas, work motivation, and support for instructional innovation, while teacher participation is relatively active but the involvement of school committees and students remains limited in strategic decision-making. Administrative transparency and accountability have been adequately implemented; however, the dissemination of information to all school stakeholders has not been optimal. The main challenges include limited time, administrative workload, and the lack of a strong participatory culture, whereas development opportunities arise from positive working relationships, community support, and leadership openness to innovation, leading to recommendations to strengthen communication systems, expand stakeholder involvement, and foster a sustainable collaborative culture.